Nicotinamide adenine dinucleotide, the sirtuins, and the secret of a long health span - Anaizi, Nasr (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
The sirtuins constitute a family of proteins with broad enzymatic activities that have an absolute requirement for nicotinamide adenine dinucleotide (NAD+) as a cosubstrate. Evidence has been mounting over the past 15 years or so that implicates the sirtuins in a vast array of critical cellular functions. In addition to transcription silencing and DNA repair, these functions include the regulation of ion channels, neuronal functions, cell growth, circadian rhythm, inflammatory response, mitochondrial biogenesis, insulin secretion, fat oxidation, and glucose metabolism. The sirtuins are critical for maintaining mitochondrial health, energy homeostasis, and redox balance. The sirtuins are widely believed to be behind the extension of lifespan brought about by calorie restriction and fasting. Changes in sirtuins activities have been linked to most age-related pathologies including cardiovascular disease, cancer, and Alzheimer's disease (AD). NAD+ is familiar to students of biological chemistry as an enzyme cofactor whose presence is essential for the progress of hundreds of vital biochemical reactions. This compound is present in virtually all living organisms. Simply put, without NAD+, life as we know it would not exist. The progress of these reactions requires the cleavage of NAD+, whose intracellular levels are known to decline steadily with age. This decline and its negative impact on the activities of these enzymes and on metabolism in general are implicated in the development of metabolic and age-linked diseases. Therefore, maintaining high intracellular NAD+ levels throughout life may not only extend the lifespan but is likely to extend the health span as well. In this paper I review how the intracellular pool of NAD+ is maintained and summarize the functions and regulation of sirtuins activities.
Keywords: Long health span; nicotinamide adenine dinucleotide; the sirtuins